Desarrollo del gametofito y del esporofito joven de Niphidium crassifolium (Filicales: Polypodiaceae s. str.) - Reyes Jaramillo, Irma (1996)
The gerrnination pattem of N. crassifolium is Vittaria-type. The prothallial development is Drynaria-type. y oung prothalli are spatulate and naked, prothalli reach maturity about 80 days afier the spore germination, with the differentiation of trichomes and gametangia. The antheridia and archegonia are typical of the leptosporangiate fems. The morphogenic development is similar to those of the many species of Polypodiaceae s.str., in particular with Campyloneurum angustifolium. The sporophyte appears 90 days afier sowing, with trichomes similar to the observed in prothalli and with branched trichomes in the petiole.